2024
DOI: 10.1111/1541-4337.13331
|View full text |Cite
|
Sign up to set email alerts
|

Designing healthier and more sustainable ultraprocessed foods

David Julian McClements

Abstract: The food industry has been extremely successful in creating a broad range of delicious, affordable, convenient, and safe food and beverage products. However, many of these products are considered to be ultraprocessed foods (UPFs) that contain ingredients and are processed in a manner that may cause adverse health effects. This review article introduces the concept of UPFs and briefly discusses food products that fall into this category, including beverages, baked goods, snacks, confectionary, prepared meals, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 311 publications
(345 reference statements)
0
3
0
Order By: Relevance
“…Strategies have been proposed, such as including these groups in food assistance programs to improve access to natural and minimally processed foods ( 2 ), as well as reformulating UPFs. However, this latter approach has been criticized by those who argue that it could legitimize and encourage the consumption of these types of products ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strategies have been proposed, such as including these groups in food assistance programs to improve access to natural and minimally processed foods ( 2 ), as well as reformulating UPFs. However, this latter approach has been criticized by those who argue that it could legitimize and encourage the consumption of these types of products ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the fortification with GS phenolics could be applied to enhance nutritional value of bean varieties with a naturally low phenolic content or to those varieties that are subjected to large phenolic losses during soaking. Moreover, there is an emerging interest in the use of beans to produce plant-based foods as meat alternatives [41,42]. It is worth noting that many foods belonging to the new generation of plant-based foods are assigned to ultra-processed foods that contain low levels of antioxidants and high levels of advanced glycation end products (AGEs), whose consumption has been linked to an array of chronic diseases [42].…”
Section: Frap Valuesmentioning
confidence: 99%
“…Moreover, there is an emerging interest in the use of beans to produce plant-based foods as meat alternatives [41,42]. It is worth noting that many foods belonging to the new generation of plant-based foods are assigned to ultra-processed foods that contain low levels of antioxidants and high levels of advanced glycation end products (AGEs), whose consumption has been linked to an array of chronic diseases [42]. Previous studies have shown that GS phenolics can inhibit the formation of AGEs [43].…”
Section: Frap Valuesmentioning
confidence: 99%